A Flavonoid-Rich Extract from Bergamot Juice, Alone or in Association with Curcumin and Resveratrol, Shows Protective Effects in a Murine Model of Cadmium-Induced Testicular Injury - Nadia Ferlazzo; Antonio Micali; Herbert Ryan Marini; Josè Freni; Giuseppe Santoro; Domenico Puzzolo; Francesco Squadrito; Giovanni Pallio; Michele Navarra; Santa Cirmi; Letteria Minutoli (MDPI AG, 2021)
It is known that cadmium damages testis structure and functionality. We examined the effects of nutraceuticals such as a flavonoid-rich extract of bergamot juice (BJe), alone or in association with curcumin (Cur) and resveratrol (Re), on mice testicular dysfunction caused by cadmium chloride (CdCl2). Controversial data on the protective effects of Cur and Re are available, while no evidence on the possible role of BJe exists. Adult male C57 BL/6J mice were administered with CdCl2 and treated with Cur, Re, or BJe alone or in combination for 14 days. Then, testes were removed and processed for molecular, structural, and immunohistochemical analyses. CdCl2 increased the mRNA of IL-1β, TNF-α, p53, and BAX while reduced that of Bcl-2 and induced tubular lesions and apoptosis of germinal cells. Cur, Re, and BJe at 40 mg/kg significantly improved all of these parameters and events, although BJe at 20 mg/kg showed a lower protective effect. The association of Cur, Re, and BJe at both doses of 50/20/20 and 100/20/40 mg/kg brought each parameter close to those of the control. Our results indicate that the nutraceuticals employed in this study and their associations exert a positive action against Cd-induced testicular injury, suggesting a possible protection of testis functionality in subjects exposed to environmental toxicants.